Liquidity creation, oil term of trade shocks, and growth volatility in Middle Eastern and North African Countries (MENA) - Ali Almeshari; Mohamed Hisham Yahya; Fakarudin Kamarudin; Rosalan Ali; Sha'ari Abd Hamid (Economies, 2023)
Both real and monetary shocks have been extensively researched, with conflicting findings on the involvement of the banking sector following the occurrence of these shocks. Nonetheless, liquidity creation (LC) appears to be one of the most underappreciated banking operations. This research analyses the impact of LC on economic volatility and the mechanisms through which LC influences volatility in 10 MENA countries from 2000 to 2019. Using a recently published panel cointegration estimating approach, we show that LC does influence growth volatility over the long term and short term-in other words, LC, as a primary activity of banks, helps to reduce volatility. According to PMG's findings, both real and monetary shocks significantly increase volatility in the short term compared to their influence in the long term. The channels of expression show that LC mitigates the influence of real shocks (amplifies the effect of monetary shocks) on growth volatility, and there is a greater magnitude of this effect in the short term. Strengthening the banking industry through LC, which is their primary business, could be a critical strategy in avoiding economic swings.
Keywords: 330; liquidity creation; growth volatility; ARDL(p; q); MENA